Boiling Heat Transfer of Nanofluids – Special Emphasis on Critical Heat Flux - Joong Kim, Sung; Kim, Hyungdae (Recent Patents on Nanotechnology, 2013)
As innovative nanotechnology-based heat-transfer media, nanofluids have evoked considerable interest among researchers owing to their improved thermal properties as well as their extendable applications to various high-power thermal systems. This paper presents a comprehensive review of recent research developments and patents pertaining to nanofluid boiling heat transfer. Nanofluids definitely offer a wide range of potential improvements in boiling heat-transfer performance. However, experimental data available from different studies are currently beset by numerous contradictions, suggesting that the fundamental mechanisms of nanofluid boiling heat transfer are not yet well understood. Consequently application of these technologies has been limited in some aspects. Only a small number of patents related to nanofluid boiling heat transfer have thus far been reported in the literature. Based on the present review, future technological development and research requirements in this area are outlined in line with technical challenges. To utilize nanofluid boiling heat-transfer technologies for practical applications, more systematic and fundamental studies are required to understand the physical mechanisms involved.
Keywords: Thermal System